Non-Operative Management of Diabetic Foot Osteomyelitis: ACase Report - Yunir, Em; Aziza, Yully Astika Nugrahayning (UI Scholars Hub, 2021)
Diabetic foot osteomyelitis is an advanced complication of diabetic foot infection which can increase the risk of amputation. This report discusses a case of a 50-year-old female with a wound on the thumb of her left foot that became more swollen with a bluish red color within one month. The patient delayed her treatment due to the COVID-19 pandemic. She has had diabetes and hypertension for 20 years which is uncontrolled. Physical examination showed a sausage toe digiti 1 left pedis with wound 4 x 2 cm with purulent discharge, Probe to Bone (PTB) positive. Laboratory and x-ray examination showed leukocytosis, increased erythrocyte sedimentation rate (ESR) and c-reactive protein (CRP), glucose level 415 mg/dL, and HbA1c 13.1%, with destruction and fragmentation in first toe bone of the left foot. Because she refused minor surgery, the wound was treated regularly by removing infected bone fragments and giving intravenous (IV) antibiotics for four weeks. For glucose level control, continuous IV insulin was given with subcutaneous basal-bolus insulin, then continued by outpatient care with oral antibiotics. After seven weeks, manifestations of infection improved, the wound area was reduced, and antibiotics were discontinued, but wound care was continued. Metabolic control along with long-term antibiotics and wound care for diabetic foot osteomyelitis can be used as an alternative to surgery